Factors that influence online purchase intention among millennial / Muhammad Hilmi Anwar - Anwar, Muhammad Hilmi (Faculty of Business and Management, 2018)
Online purchase is the process of buying things either products or services through the Internet. It is growing rapidly every year throughout the world. In Malaysia, it have been ranked 9th as the most popular reason for people to go online by Malaysia Communication and Multimedia Commision. Most of the people who have experience with purchasing online are millennial which mean born between 1977 and 2000. Throughout this study, the researcher will investigate what are the factors that influence the millennial to purchase online. The independent variables are perceived usefulness, perceived ease of use, electronic word of mouth and trust while the dependent variable is online purchase intention. A set of 248 questionnaire were distributed and the data collected will be analyzed using Statistical Package for Social Sciences (SPSS) version 23. The findings shows that perceived usefulness, electronic word of mouth and trust have strong influence with millennial intention towards online purchasing. Perceived ease of use did not have significance towards millennial online purchase intention.